2016
DOI: 10.3399/bjgp16x683857
|View full text |Cite
|
Sign up to set email alerts
|

‘I’m fishing really’ — inflammatory marker testing in primary care: a qualitative study

Abstract: BackgroundInflammatory markers can be helpful as part of the diagnostic workup for specific diseases or for monitoring disease activity. A third use is as a screening and/or triage tool to differentiate between the presence or absence of disease. Most research into inflammatory markers looks at diagnosis of specific diseases and comes from secondary care. Qualitative studies to explore when and why clinicians use these tests in primary care are lacking.AimTo identify clinicians’ approaches to inflammatory mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Unlike for the NC, we observed that the proportion of patients who underwent a CRP test increased from younger to older age groups. Diagnosis in the older age groups may be more difficult because of non-specific presentations (such as absence of fever with infection)33 and GPs may be using CRP in addition to the NC to screen for serious illness 9. Potentially, the availability of portable CRP devices may be very beneficial in assisting the diagnosis in older frail or housebound patients for whom access to blood tests is more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike for the NC, we observed that the proportion of patients who underwent a CRP test increased from younger to older age groups. Diagnosis in the older age groups may be more difficult because of non-specific presentations (such as absence of fever with infection)33 and GPs may be using CRP in addition to the NC to screen for serious illness 9. Potentially, the availability of portable CRP devices may be very beneficial in assisting the diagnosis in older frail or housebound patients for whom access to blood tests is more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis of 14 randomised controlled trials investigating the effect of diagnostic tests for patients with a low pretest probability of serious illness (presenting with symptoms such as fatigue and low back pain) reported that testing did little to reassure patients, decrease their anxiety, or resolve their symptoms, although tests did reduce further visits to primary care 10. Qualitative research highlights diagnostic uncertainty in relation to non-specific symptoms as a common reason for inflammatory marker testing, with the aim to reassure 11. However, inconclusive results can paradoxically generate a cycle of uncertainty and anxiety 1112…”
mentioning
confidence: 99%
“…Qualitative research highlights diagnostic uncertainty in relation to non-specific symptoms as a common reason for inflammatory marker testing, with the aim to reassure 11. However, inconclusive results can paradoxically generate a cycle of uncertainty and anxiety 1112…”
mentioning
confidence: 99%
“…4 All of this can contribute to our everspiralling workloads, as Des Spence has recently highlighted. 7 Another GP we interviewed described the impact:…”
mentioning
confidence: 99%
“…Unfortunately this can lead to a vicious cycle; rather than reassuring ourselves, inconclusive or borderline results can generate increased uncertainty and anxiety. 4 This in turn can lead to cascades of further tests, in what has been termed 'investigation momentum': the relentless pursuit to resolve uncertainty. 5 Testing to 'reassure patients'.…”
mentioning
confidence: 99%